Civil Conflict, Stress and Children - Gibson, Kerry (PINS-Psychology in Society, 2025)
The South African political crisis of 1985/6 has created a sense of urgency around the need to conduct research into the psychological effects of its stressful events. The probable detrimental effects of an environment of civil conflict on children has constituted an area of particular concern. This is reflected in the fears voiced by township residents for their children (see Richman, 1986); in media reports which illustrate the events to which children are being exposed (see Jacobs and Hollinghead, 1985, for a summary of relevant press reports); and by clinicians in their work with the childhood ’victims’ of these stressful events (Swartz et al., 1986).